Combinatorial Application of Hyaluronic Acid and Curcumin-Albumin Conjugate for Cartilage Repair in TNF- α Induced Inflammation in Rabbit Knee Joint - Sathee, Deepa; Shenoy, Sachin J; Anil, Arya; A, Sabareeswaran; Krishnan, Lissy Kalliyana (Archives of Clinical and Biomedical Research, 2021)
Osteoarthritis has emerged as a consequential disorder resulting from changing lifestyles, especially in the aged population. It is one of the most devastating degenerative joint diseases caused due to inflammation, wear and tear of articular cartilage leading to irreversible damage and physical trauma. Several intra-articular formulations are experimented with for restoring damaged cartilage. Many of them failed because of minimal effectiveness in establishing long-term therapeutic potential. We explored the cartilage regeneration potential of Hyaluronic acid (HA) on combining with dimethoxy curcumin-human serum albumin (DMCHSA) conjugate upon intra-articular administration. HA is known to possess immense lubrication property and is a well-recognized visco-supplement. The DMCHSA has the potential to suppress the action of inflammatory markers. So, a combinatorial approach anticipates an ideal therapeutic strategy to overcome the demerits of existing interventions. Intra-articular injection of Tumor Necrosis Factor-α (TNF-α), repeatedly at 7-day intervals disrupted the cartilage morphology and produced an inflammatory knee joint model to study the therapeutic potential of DMCHSA-HA combination. Into separate inflamed knee-joint cartilage HA, DMCHSA and DMCHSA-HA were administered periodically to highlight the advantage of mixing the latter with the former. Histopathology and gene expression analysis assessed the restoration potential of the treatment. We observed remarkable restoration of degenerated cartilage upon treatment with the DMCHSA-HA combination. The columnar arrangement of cells, regulated deposition of ECM components such as glycosaminoglycans (GAGs) & collagen, and synchronized expressions of inflammatory marker molecules suggested restoration of the treated defects. The treatments with DMCHSA, HA, or HSA alone seemed inferior to DMCHSA-HA combination therapy. The study confirme